DEVELOPING PUBLIC SPEAKING AND JOB INTERVIEW SKILLS FOR HOSPITALITY STUDENTS - Septi Fahmi Choirisa; Ringkar Situmorang; Yoanita Alexandra; Intan Primadini (Jurnal Sinergitas PKM & CSR, 2022)
The main issues this article tries to address are vocational students' self-development skills. As a part of the tourism and hospitality industry, vocational schools and university students and lecturers are working on how the next generations contribute to supporting the government's aim to have sustainable business growth. Many vocational schools cover hard skills with low attention to students’ soft skills development. There is a massive gap between their self-preparations and their capabilities in technical management. This reality makes students less motivated and confident to compete in the workforce. This method employed pre-evaluations, workshops, a coaching clinic, and post-event evaluation to ensure the fulfilment of students’ needs. From the first to the second quarter of 2022, this program was made to develop students at Public Vocational School 7 Tangerang, Indonesia. With a total of 110 students with teachers involved, the workshop fulfilled students’ needs in the pre-evaluation questionnaire. Most of the students were satisfied and rated that this workshop supported their preparation before join to the hotel industry. This article contributes to hotel vocational school literature, especially in soft skill development. Moreover, issues addressed in this article can be an insight for vocational school management.